The Economic Optimality of Sanction Mechanisms in Interorganizational Ego Networks – A Game Theoretical Analysis – - Muhamed Kudic; Marc Banaszak (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2009)
Even though small- and medium-sized firms (SMEs) were believed not to proceed beyond exporting in their internationalization routes, we can observe new types of co-operation intensive entrepreneurial firms – so-called “micromultinational enterprises” (mMNEs) – entering the global landscape. These firms face the challenge to manage and control a portfolio of national and international alliances simultaneously (ego network). The aim of this paper is to provide game theoretically consolidated conditions in order to analyze the effectiveness and efficiency of interorganizational sanction mechanisms in an alliance portfolio setting. A game theoretical framework is developed over three stages with increasing complexity. Results show that two out of six analyzed sanction mechanisms do not fulfill the game theoretical condition for effectiveness. The efficiency analysis sensibilizes for discretionary elements in governance structures and demonstrates that not one single sanction mechanism but rather the right choice and combination of different types of sanction mechanisms leads to efficient results. We contribute to the international business, alliance, and network literature in several ways by focusing on alliance portfolios held by mMNEs. In doing so, we move beyond the dyadic level and analyze sanction mechanisms from an ego network perspective, a still widely under-emphasized topic in the literature. – – Obwohl bisher vielfach davon ausgegangen wurde, dass die Internationalisierungspfade kleiner und mittlerer Unternehmen (KMU) über Exportaktivitäten nicht hinausgehen, lässt sich das Erscheinen einer neuen Gattung von global agierenden Gründungsunternehmen, die intensive Kooperationskonstellationen unterhalten, so genannte micromultinational enterprises (mMNEs), beobachten. Diese Unternehmen stehen vor der Herausforderung, ein Portfolio, bestehend aus einer Vielzahl nationaler und internationaler Allianzen, simultan zu koordinieren (Egonetzwerk). Diese Arbeit verfolgt das Ziel, spieltheoretische Bedingungen zur Analyse der Effektivität und Effizienz von Sanktionsmechanismen in Allianzportfolios herzuleiten. Zu diesem Zweck verwenden wir ein einfaches spieltheoretisches Grundmodell und erweitern dieses über drei Stufen mit steigender Komplexität. Die Ergebnisse zeigen, dass zwei von sechs analysierten Sanktionsmechanismen die spieltheoretische Effektivitätsbedingung nicht erfüllen. Die Effizienzanalyse sensibilisiert für Problematiken, die mit diskretionären Elementen in Governance-Strukturen verbunden sind, und zeigt, dass nicht ein einzelner Sanktionsmechanismus, sondern die richtige Wahl und Kombination verschiedener Sanktionen zu effizienten Resultaten führt. Wir tragen mit unserer Arbeit zur Internationalen Business, Allianz und Netzwerkliteratur bei, indem wir den Fokus auf Allianzportfolios in mMNEs lenken. Statt einer dyadisch orientierten Perspektive legen wir bei der Analyse von Sanktionsmechanismen eine Egonetzwerkperspektive zugrunde und wenden uns damit einem bisher weitestgehend unbehandelten Themenkomplex zu.
urn:nbn:de:101:1-200911033203
Keywords: L14; L22; L24; M21; 330; alliance portfolio; ego network; governance; sanctions; game theory; Allianzportfolio; Egonetzwerk; Governance; Sanktionen; Spieltheorie; Business Network; Klein- und Mittelunternehmen; Internationale Unternehmenskooperation; Multinationales Unternehmen; Corporate Governance; Spieltheorie; Theorie